Academic Advisors and Their Diverse Advisees: Towards More Ethical Global Universities - Ikegami Lee, Yuko; Metcalfe, Amy (Journal of International Students, 2017)
In this comparative content analysis, job postings for academic advising personnel from U.S. and Canadian higher education institutions were examined to ascertain expectations for job candidates in terms of skills and duties, educational requirements, and compensation. Fifty-three job descriptions from 18 research-intensive, public universities were collected for this study. The findings show that institutions expect academic advisors to be multitalented and skilled professionals, but that calls for experience working with international students are limited, despite the rising importance of internationalization in higher education.